Characterisation of Ramularia collo‐cygni laboratory mutants resistant to succinate dehydrogenase inhibitors. Issue 6 (16th November 2016) - Piotrowska, Marta J; Fountaine, James M; Ennos, Richard A; Kaczmarek, Maciej; Burnett, Fiona J
Abstract: BACKGROUND: Ramularia collo‐cygni ( Rcc ) is responsible for Ramularia leaf spot (RLS), a foliar disease of barley contributing to serious economic losses. Protection against the disease has been almost exclusively based on fungicide applications, including succinate dehydrogenase inhibitors (SDHIs). In 2015, the first field isolates of Rcc with reduced sensitivity to SDHIs were recorded in some European countries. In this study we established baseline sensitivity of Rcc to SDHIs in the United Kingdom and characterised mutations correlating with resistance to SDHIs in UV‐generated mutants. RESULTS: Five SDHI‐resistant isolates were generated by UV mutagenesis. In four of these mutants a single amino acid change in a target succinate dehydrogenase (Sdh) protein was associated with decrease in sensitivity to SDHIs. Three of these mutations were stably inherited in the absence of SDHI fungicide, and resistant isolates did not demonstrate a fitness penalty. There were no detectable declines in sensitivity in field populations in the years 2010–2012 in the United Kingdom. CONCLUSIONS: SDHIs remained effective in controlling Rcc in the United Kingdom in the years 2010–2012. However, given that the first isolates of Rcc with reduced sensitivity appeared in other European countries in 2015, robust antiresistance strategies need to be continuously implemented to maintain effective disease control. © 2016 Society of Chemical Industry